If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -3c = 3 Solving 24 + -3c = 3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -3c = 3 + -24 Combine like terms: 24 + -24 = 0 0 + -3c = 3 + -24 -3c = 3 + -24 Combine like terms: 3 + -24 = -21 -3c = -21 Divide each side by '-3'. c = 7 Simplifying c = 7
| x^2-27x+1=0 | | 13-13=2w | | 22+3n=88 | | 21=x+7x+5 | | T+8.3=2.67 | | 8(y+2)=72 | | -6x-8+2x=-8 | | -9+3t+2t^2=0 | | 4q+8=16 | | V-d=3 | | 5x+1-6x=9 | | 14-b=68 | | 9-5x+2x=-18 | | x^2+27x+1=0 | | x+6+x=-6 | | 4(w-87)=44 | | -5x-9+6x=-20 | | 0.6(5x+15)=2.4-(x+3) | | 6(3x+8)+4=18x+52 | | 4y=20x+16 | | -7(x-3)+8=1 | | -2(y+6)+-6=-6 | | 7x+3-5x=3 | | 5X-12=-30 | | 6+4(x-7)=10-5(x-7) | | 2x-x=132 | | 6(4-x)+6x=64 | | 2+3k=8 | | 2[8+2(x-3)]=16 | | 5x+17=21 | | -60=2x+3x-10 | | 3-4x+2=14 |